Comparison of the effects of a liquid breakfast meal with varying doses of plant-based soy protein on appetite profile, energy metabolism and intake. (1st October 2019) - Nepocatych, Svetlana; Melson, Caroline E.; Madzima, Takudzwa A.; Balilionis, Gytis
Abstract: A dose dependent satiating and thermogenic effect of animal-based protein has been observed, however, less is known wherever plant-based protein elicits same response. The purpose of the study was to examine the effects of a breakfast meal containing varying doses of plant-based soy protein (SP) on appetite profile, hormone response, energy metabolism and energy intake. METHODS: Seventeen participants (age: 27 ± 7 y, body fat: 21.5 ± 6.9%) in randomized order consumed one of three isoenergetic liquid breakfast meals (482 ± 5 kcals): high SP (HSP; 50 g), low SP (LSP; 25 g) and control (CON; 50 g carbohydrate) followed by an ad libitum lunch 3 h later. Appetite profile was measured before, immediately after and hourly during the 3 h postprandial period. Plasma concentrations of leptin and insulin were measured before, at 30 and 180 min. RESULTS: Energy intake at lunch per kilogram of body weight was significantly higher after CON (11 ± 3.6 kcal/kg) compared to HSP (9.1 ± 3.0 kcal/kg) but not compared to LSP (10.2 ± 2.7 kcal/kg). Participants hunger was higher, whereas, satiety and fullness were lower after CON ( p  < 0.05). There were no significant differences ( p  > 0.05) observed in leptin or insulin responses between meals, however, a significant change over time was observed for insulin (p = 0.02) but not leptin ( p  > 0.05). CONCLUSION: Liquid breakfast meals with higher dose of soy protein reduced energy intake when adjusted by body weight at lunch and was rated as more satiating compared to an isoenergetic CON meal.